Female genital tract tuberculosis in Tribhuvan University Teaching Hospital: A retrospective one year histopathological study - Jha, Abhimanyu; Sayami, Gita; Adhikari, Ram; Jha, Roona; Chaudhari, Rashmi (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Aim: To determine frequency of female genital tract (FGT) tuberculosis (TB) in the gynecological biopsies received in the Department of Histopathology of Tribhuvan University Teaching Hospital. Methods: This is a retrospective study conducted in the Department of Pathology of Tribhuvan University Teaching Hospital. Histopathology records of one year (14th April 2006 to 13th April 2007) were retrieved and searched for the cases of female genital tract TB. Relevant histopathological findings and clinical data were recorded and analyzed. Results: We analyzed 5696 histopathological cases during one year period for FGT tuberculosis. There were 1565 cases of gynecological biopsy and 9 cases were diagnosed as FGT tuberculosis based on histopathological and clinical findings. Ovarian tuberculosis was seen in three cases, bilateral fallopian tubes were involved in 2 cases and endometrial tuberculosis was diagnosed in 2 cases. 3 cases of omental biopsy and 1 case of peritoneal biopsy showed tubercular granulomas. Conclusion: FGT tuberculosis was usually seen in age 16-28 years and constituted 0.57% of total gynecological cases and 0.15% of total biopsies. Fallopian tubes, ovaries and endometrium were affected with the involvement of peritoneum or omentum, common event being tubercular endosalpingitis. Histopathology in association with clinical findings still remains gold standard for the diagnosis of FGT tuberculosis in our country despite advancement in diagnostic modalities; however, incidental histological detection in clinically unanticipated cases is not an uncommon event. Key Words: Female genital tract TB, histopathology, clinical findings. doi:10.3126/njog.v2i2.1452 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 29 - 34